Gastrodin inhibits reactive astrocyte-mediated inflammation in hypoxic-ischemic brain damage through S100B/RAGE-Smad3 signaling - Wang Pengxiang; Zuo Hanjun; Shi Haolong; Wang Zhao; Ren Xueqi; Shi Jinsha; Guo Tao; Kuang Xianfeng; Zhao Min; Li Jinghui; Li Juanjuan (Acta Biochimica et Biophysica Sinica)
Activated astrocytes and their associated inflammatory responses play critical roles in the pathogenesis of hypoxic-ischemic brain damage (HIBD). Gastrodin (GAS), an anti-inflammatory herbal agent, is known to suppress microglial activation. Here, we investigate whether it exerts a similar effect on activated astrocytes and whether it acts through S100B/RAGE-Smad3 signaling. The expression changes of S100B/RAGE-Smad3 signaling pathway-related proteins, inflammatory factors and A1/A2 astrocyte markers were detected by ELISA, western blot analysis, immunofluorescence and immunohistochemistry. The results show that GAS decreases the expression of sRAGE in the brain tissue and S100B in the serum and brain tissue of HIBD mice. However, it promotes the expression of sRAGE in the serum of HIBD mice. Moreover, GAS inhibits the expressions of RAGE, p-Smad3, TNF-α, and C3 (A1 astrocyte marker), and promotes the expressions of S100A10 (A2 astrocyte marker) and BDNF in HIBD model mice, as well as in oxygen glucose deprivation (OGD)-treated TNC-1 astrocytes. The immunofluorescence and immunohistochemical results of RAGE and p-Smad3, as well as the immunofluorescence results of C3 and S100A10, reveal the same trend. Interestingly, FPS-ZM1 (a specific inhibitor of RAGE) inhibits the expressions of p-Smad3, TNF-α, C3, and S100A10, but promotes that of BDNF compared with those in the OGD group. The combination of GAS and FPS-ZM1 further decreases the expression of C3. These results indicate that GAS can inhibit the activation of Smad3 through S100B/RAGE signaling and regulate the expression of A1/A2-type astrocytes.